Non-verbal behaviors-performance relationship among a sample of international table tennis players - Ledos, S.; Martinent, G.; Decret, J.-C.; Nicolas, M. (International Journal of Table Tennis Sciences, 2013)
The main aim of this study was to examine the relationship between non-verbal behaviors of high level table tennis players and their performance during high-stakes table tennis matches. This study also provided descriptive evidence relating to the nature and frequency of the non-verbal behaviors expressed by athletes while competing. Eight high-level matches from the European Top 12 and French pro A championship for a total of 13 different players ranking 10th-161st on the world ITTF ranking at the moment of the study were analyzed. Coding grid allowed researcher to extract the following quantitative variables from the videotapes of high-stakes table tennis matches: (1) nature of non-verbal behaviors deployed by table tennis players during competition, (2) frequency of non-verbal behaviors deployed by table tennis players during competition, (3) gain vs. loss of match, (4) gain vs. loss of game, (5) gain vs. loss of the previous point, and (6) gain vs. loss of the next point. Quantitative analyses of the videotapes revealed the presence of 25 specific non-verbal behaviors, for a total of 4972 non-verbal behaviors observed during the matches. Results showed that the frequency of non-verbal behaviors was significantly different between: (1) matches won vs. lost, (2) games won vs. lost, (3) previous points won vs. lost, and (4) next points won vs. lost. Particular non-verbal behaviors seem thus to have a causal influence on the result of the next point (won vs. lost). Specifically, players who "run around the playing area" would increase their chances to win the next point. Contrary, players who "remake the gesture" and/or "touch/scratch his face" would decrease their chances to win the next point. The predominant focus in sport psychology has been on pre-performance non-verbal behaviors, with far less attention paid to the non-verbal behaviors expressed by athletes during competition. Support was provided for the usefulness to examine the wide range of non-verbal behaviors expressed by international table tennis players during the competition as well as for their significant influence on the performance of players while competing.